Happiness at work enhancement for municipality city officers model - ลือชา, ธิดารักษ์; นันทเพ็ชร, กฤษฎา; ไกรวาส, กิจฐเชต (Academic Journal Phranakhon Rajabhat University, 2018)
The purpose of this research study were to 1) to study about happiness at work of city municipality officers, 2) develop model of happiness at work enhancement for city municipality officers , 3) test the consistency of model with an observed set of data. The sample group are 394 officers in 29 cities municipality.The quantitative analysis employed in this study was descriptive statistics, percentage, and standardized score. The confirmatory factor analysis was used to test the consistency of model with an observed set of data. The structural equation model analysis was applied for analyzing the causal relations between variables in the conceptual model. The results of the study revealed that 1) The level of happiness at work of city municipality officers were high. The level of happiness at work in satisfaction at work and work engagement were high level, organizational commitment was medium level. 2) Model of happiness at work enhancement for city municipality officers consisted of 6 latent and 15 observed variables. Latent variables in model were happiness at work, leadership, human resource management, placing, enhancement of healthy and enhancement of life style. Observed variables of happiness at work were satisfaction at work, work engagement and organizational commitment. Observed variables of leadership were idealized influence, inspiration motivation, intellectual stimulation and individualized consideration. Observed variables of human resource management were high performance work practices and organizational justice. Observed variables of placing were physical placing and ethical climate in organization. Observed variables of enhancement of healthy were physical health enhancement and mental health enhancement. Observed variables of enhancement of life style were financial enhancement and family relationship enhancement. 3) The results of the confirmatory factor analysis revealed that the predefined factor model was appropriate to the empirical data in good fit (X2 / DF in model was 1.891 while GFI = .953, AGFI = .925 CFI = .984 and RMSEA = .048). 4) The results of the structural equation model analysis indicated that leadership, human resource management had positive direct effects to happiness at work with significant .01. Placing had positive direct effects to happiness at work with significant .05.